PHYSICAL THERAPY MANAGEMENT OF SCHATZKER TYPE VI TIBIAL PLATEAU FRACTURE POST ORIF: A CASE REPORT - M Irfan Alhady; Arif Pristianto; Prihantoro Larasati (Sekolah Tinggi Ilmu Kesehatan (STIKes) Cirebon, 2026)
Tibial plateau fractures are complex intra-articular injuries that frequently result in pain, edema, restricted knee range of motion, and functional limitations, particularly in severe cases such as Schatzker type VI fractures, commonly managed with Open Reduction and Internal Fixation (ORIF) using double plate fixation. This case report aimed to describe physiotherapy management and clinical outcomes in a patient with left knee motion limitation following a Schatzker type VI tibial plateau fracture after ORIF. A case report design was applied to a 23-year-old female patient diagnosed with a closed left tibial plateau fracture Schatzker type VI, post ORIF with double plate. The physiotherapy program consisted of infrared therapy for pain management, muscle release techniques to reduce soft tissue tightness, range of motion (ROM) exercises using a closed kinetic chain approach, progressive quadriceps strengthening, and gait training with a 3-point gait pattern according to the healing phase. Clinical outcomes were evaluated periodically using the Numerical Pain Rating Scale (NPRS), ROM measurements, the figure-of-eight method for edema, Manual Muscle Testing (MMT), and the Lower Extremity Functional Scale (LEFS). The results demonstrated a reduction in pain and edema, significant improvements in knee joint ROM, increased quadriceps muscle strength, and enhanced functional ability reflected by improved LEFS scores and greater independence in mobility. This case report concludes that a structured, progressive, and multimodal physiotherapy approach plays a crucial role in restoring knee function and improving functional outcomes following ORIF in patients with Schatzker type VI tibial plateau fractures Abstrak: Fraktur tibial plateau merupakan cedera intra-artikular kompleks yang sering menyebabkan keterbatasan gerak sendi lutut, nyeri, edema, dan penurunan kemampuan fungsional, terutama pada fraktur berat seperti Schatzker tipe VI yang umumnya ditangani dengan Open Reduction and Internal Fixation (ORIF) menggunakan double plate. Laporan kasus ini bertujuan untuk mendeskripsikan penatalaksanaan fisioterapi serta respons klinis pasien dengan keterbatasan gerak knee sinistra pasca ORIF fraktur tibial plateau Schatzker tipe VI. Penelitian menggunakan desain case report pada seorang pasien perempuan berusia 23 tahun dengan diagnosis closed fracture tibia plateau sinistra Schatzker tipe VI post ORIF dengan double plate. Intervensi fisioterapi yang diberikan meliputi modalitas infrared untuk manajemen nyeri, muscle release untuk mengurangi ketegangan jaringan lunak, latihan rentang gerak sendi (range of motion/ROM) dengan pendekatan closed kinetic chain, penguatan otot quadriceps, serta edukasi dan latihan gait menggunakan pola 3-point gait sesuai fase penyembuhan. Evaluasi dilakukan secara berkala menggunakan Numerical Pain Rating Scale (NPRS), pengukuran ROM, figure of eight untuk edema, Manual Muscle Testing (MMT), dan Lower Extremity Functional Scale (LEFS). Hasil menunjukkan penurunan nyeri dan edema, peningkatan lingkup gerak sendi lutut, peningkatan kekuatan otot quadriceps, serta perbaikan kemampuan fungsional yang ditandai dengan peningkatan skor LEFS dan kemandirian mobilisasi pasien. Kesimpulan dari laporan kasus ini menunjukkan bahwa penatalaksanaan fisioterapi yang terstruktur, bertahap, dan multimodal berperan penting dalam mendukung pemulihan fungsi lutut dan meningkatkan kualitas aktivitas fungsional pasien pasca ORIF fraktur tibial plateau Schatzker tipe VI.